Digitalisation concept for personalised assembly information at Volvo Cars - Puranjay, Mugar; Pravin Kumar, Ravichandran (My University, 2024)
The onset of mass customization and personalization trends within automobile man ufacturing has led to an increase in assembly complexity. High variations within the final assembly stages demand a higher operator cognition in order to maintain quality and efficiency standards. To maintain production excellency, adequate in formation and support is required during production. With the rise of digitalization within the Industry 4.0 paradigm, providing personalized assembly information and assistive alerts digitally can potentially assist operators in their daily work and lower cognitive workloads. Thus, resulting in better quality and efficiency. This thesis investigates a digitalization concept for the presentation of personalized assembly information and the generation of assistive alerts via a digital worker infor mation system. By adopting a mixed method approach centred around operators, the study focuses on understanding how available assembly information and differ ent support functions can be digitalized to offer cognitive support. The outcome involved creating a conceptual representation of personalized assembly information for a worker information system from what is deemed important for a moving line scenario. The most optimal presentation for digital assembly information involves displaying variant-specific information for an operator working at a particular workstation. To support operators with quality, personalized assistive alerts based on their history of quality deviations displayed at the start of production (during operators’ login as offline alerts) and during running production (as online alerts), can potentially aid operators in being mindful of their mistakes and remind them towards working in a standardized manner. The generation of personalised information and alerts will depend on employing a suitable system architecture (like a microservice archi tecture) that enables real-time streaming of data based on events occurring on the assembly line. The implication of such a setup potentially opens new possibilities for digital operator support within complex production environments.